Protection of Human Lens Epithelial Cells from Oxidative Stress Damage and Cell Apoptosis by KGF-2 through the Akt/Nrf2/HO-1 Pathway. (17th February 2022) - Liu, Shuyu; Jin, Zi; Xia, Ruyue; Zheng, Zhuoni; Zha, Yi; Wang, Qiang; Wan, Xinbei; Yang, Hui; Cai, Jianqiu
Abstract : Oxidative stress exerts a significant influence on the pathogenesis of various cataracts by inducing degradation and aggregation of lens proteins and apoptosis of lens epithelial cells. Keratinocyte growth factor−2 (KGF-2) exerts a favorable cytoprotective effect against oxidative stress in vivo and in vitro . In this work, we investigated the molecular mechanisms of KGF-2 against hydrogen peroxide- (H2 O2 -) induced oxidative stress and apoptosis in human lens epithelial cells (HLECs) and rat lenses. KGF-2 pretreatment could reduce H2 O2 -induced cytotoxicity as well as reactive oxygen species (ROS) accumulation. KGF-2 also increases B-cell lymphoma-2 (Bcl-2), quinine oxidoreductase-1 (NQO-1), superoxide dismutase (SOD2), and catalase (CAT) levels while decreasing the expression level of Bcl2-associated X (Bax) and cleaved caspase-3 in H2 O2 -stimulated HLECs. LY294002, the phosphatidylinositol-3-kinase (PI3K)/Akt inhibitor, abolished KGF-2's effect to some extent, demonstrating that KGF-2 protected HLECs via the PI3K/Akt pathway. On the other hand, KGF-2 activated the Nrf2/HO-1 pathway by regulating the PI3K/Akt pathway. Silencing nuclear factor erythroid 2-related factor 2 (Nrf2) by targeted-siRNA and inhibiting heme oxygenase-1 (HO-1) through zinc protoporphyrin IX (ZnPP) significantly decreased cytoprotection of KGF-2. Furthermore, as revealed by lens organ culture assays, KGF-2 treatment decreased H2 O2 -induced lens opacity in a concentration-dependent manner. As demonstrated by these data, KGF-2 resisted H2 O2 -mediated apoptosis and oxidative stress in HLECs through Nrf2/HO-1 and PI3K/Akt pathways, suggesting a potential protective effect against the formation of cataracts.